Suction evacuation of hemothorax: A prospective study. Issue 1 (July 2016) - Savage, Stephanie A.; Cibulas, George A.; Ward, Tyler A.; Davis, Corinne A.; Croce, Martin A.; Zarzaur, Ben L.
Abstract : BACKGROUND: Although tube thoracostomy is a common procedure after thoracic trauma, incomplete evacuation of fluid places the patient at risk for retained hemothorax. As little as 300 to 500 cm 3 of blood may result in the need for an additional thoracostomy tube or, in more severe cases, lung entrapment and empyema. We hypothesized that suction evacuation of the thoracic cavity before tube placement would decrease the incidence of late complications. METHODS: Patients requiring tube thoracostomy within 96 hours of admission were prospectively identified and underwent suction evacuation of the pleural space (SEPS) before tube placement. These patients were compared to historical controls without suction evacuation. Demographics, admission vital signs, laboratory values, details of chest tube placement, and outcomes were collected on all patients. Multivariable logistic regression was used to compare outcomes between groups. RESULTS: A total of 199 patients were identified, consisting of 100 retrospective controls and 99 SEPS patients. There were no differences in age, sex, admission injury severity score or chest abbreviated injury score, admission laboratory values or vital signs, or hospital length of stay. Mean (SD) volume of hemothorax in SEPS patients was 220 (297) cm 3 ; with only 48% having a volume greater than 100 cm 3 at the time of tube placement. Three patients developed empyema, and 19 demonstrated retained blood; there was no difference between SEPS and control patients. Suction evacuation of the pleural space was significantly protective against recurrent pneumothorax after chest tube removal (odds ratio, 0.332; 95% confidence interval, 0.148–0.745). CONCLUSION: Preemptive suction evacuation of the thoracic cavity did not have a significant impact on subsequent development of retained hemothorax or empyema. Suction evacuation of the pleural space significantly decreased incidence of recurrent pneumothorax after thoracostomy removal. Although the mechanism is unclear, such a benefit may make this simple procedure worthwhile. A larger sample size is required for validation and to determine if preemptive thoracic evacuation has a clinical benefit. LEVEL OF EVIDENCE: Therapeutic/care management study, level IV.